2017
DOI: 10.1002/chem.201701939
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cell and Bulk Cancer Cell Active Copper(II) Complexes with Vanillin Schiff Base Derivatives and Naproxen

Abstract: Four copper(II) complexes, 1-4 containing regioisomeric vanillin Schiff base derivatives and the nonsteroidal anti-inflammatory drug (NSAID), naproxen, were synthesised and characterised. All complexes effectively cleave DNA in cell-free systems, with 4 displaying the highest nuclease activity. DNA binding studies suggest that 4 binds to DNA via the grooves prior to inducing oxidative DNA cleavage. Three of the complexes (1, 3, and 4) indiscriminately kill cancer stem cell (CSC)-enriched cells (HMLER-shEcad) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 54 publications
3
34
0
Order By: Relevance
“…Most of the CSC specific small molecules undergoing clinical trials are organic in nature, 7 however, we and others have shown that metal complexes also display attractive anti-CSC and -bulk cancer cell properties. [8][9][10][11][12][13][14][15] Our previous work has shown that reactive oxygen species (ROS) elevation in combination with cyclooxygenase-2 (COX-2) inhibition by mononuclear copper(II)-nonsteroidal antiinflammatory drug (NSAID) complexes enables CSC and bulk cancer cell toxicity. 9,10,13 The success of this strategy is attributed to the vulnerability of CSCs and bulk cancer cells to changes in their intracellular redox state 16,17 and the overexpression of COX-2 18,19 in certain CSCs and bulk cancer cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the CSC specific small molecules undergoing clinical trials are organic in nature, 7 however, we and others have shown that metal complexes also display attractive anti-CSC and -bulk cancer cell properties. [8][9][10][11][12][13][14][15] Our previous work has shown that reactive oxygen species (ROS) elevation in combination with cyclooxygenase-2 (COX-2) inhibition by mononuclear copper(II)-nonsteroidal antiinflammatory drug (NSAID) complexes enables CSC and bulk cancer cell toxicity. 9,10,13 The success of this strategy is attributed to the vulnerability of CSCs and bulk cancer cells to changes in their intracellular redox state 16,17 and the overexpression of COX-2 18,19 in certain CSCs and bulk cancer cells.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Our previous work has shown that reactive oxygen species (ROS) elevation in combination with cyclooxygenase-2 (COX-2) inhibition by mononuclear copper(II)-nonsteroidal antiinflammatory drug (NSAID) complexes enables CSC and bulk cancer cell toxicity. 9,10,13 The success of this strategy is attributed to the vulnerability of CSCs and bulk cancer cells to changes in their intracellular redox state 16,17 and the overexpression of COX-2 18,19 in certain CSCs and bulk cancer cells. Here, we have sought to improve CSC and bulk cancer cell activity by developing tetranuclear copper(II) complexes bearing multiple diclofenac moieties (a COX-2 inhibitor with anti-metastatic potential) 20,21 and Schiff base ligands (a wellknown ROS mediator once coordinated to copper).…”
mentioning
confidence: 99%
“…Breast cancer MDA-MB-231 cells, in which Ru(II) and Os(II) complexes 1 and 2 (Fig. 1) have shown excellent antiproliferative activity 10 , are unable to form long-term mammosphere cultures (forming rather amorphous aggregates instead of compact spheroids in serum free spheroid suspension culture) 15 . Therefore, next we used hBCSC enriched human breast cancer cell lines (MCF-7 CD44+/CD24− and SKBR-3 CD44+/CD24− ) as more convincing CSC models to assess the CSC specificity of the Ru(II) and Os(II) complexes 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The study of Schiff base compounds and their metal complexes has become an important branch of synthetic organic chemistry due to their extensive biological activities, which include anticancer, antibacterial and antiviral effects [8,9]. Numerous studies have reported that Schiff base compounds can effectively eliminate stem cell-enriched cancer cells (HMLER-shEcad) and bulk cancer cells (HMLER) [10] induce apoptosis to inhibit gastric tumor growth [11], and signi cantly inhibit the growth of various human carcinoma cell lines derived from lung (A-549), breast (MDA-MB-231) and colon (LS174T) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%